Historical dynamics of Indonesian halal products certification: shifting roles between state and religious institutions - Fathurrohman, Yusuf E.; Kontor, Eniko (Journal of the Belarusian State University. History, 2026)
Halal products regulation in Indonesia has undergone a profound transformation, evolving from informal religious practices into a complex state-regulated system. This study aims to trace the historical development of halal governance in Indonesia, positioning it within a long-term development that moves from community-based practices and the informal religious authority of scholars (ulama) to the contemporary state-led halal regulatory system. Employing a methodic of combination of normative-legal approach and historical synthesis, this research examines scholarly literature and official state regulations to reconstruct the regulatory trajectory. The findings reveal that halal regulation evolved through following distinct phases: the early phase of socially embedded practices driven by community norms, the transitional institutionalisation phase (1976–2014) marked by state and Ministry of Religious Affairs of the Republic of Indonesia collaboration and the current state-centric regime under the halal product assurance law.